Improving the practice of real estate e-auction in Malaysia: an exploratory study / Syahmimi Ayuni Ramli ... [et al.] - Ramli, Syahmimi Ayuni; Alias, Muhammad Nazim; Arshad, Huraizah; Mohammad, Izran Sarrazin (UiTM Press, 2024)
Nowadays, internet auctions are employed instead of traditional auction procedures. This is attributed to information and computer technology advancements, e-commerce technologies, a vast catchment market, and other considerations. The online real estate auction has been used globally and in Malaysia. The High Court of Malaya now uses the EAuction System for public real estate auctions in Malaysia. However, EAuction practice in Malaysia has been asked to be discontinued since it interferes with the auctioneer's profession, and bidder data privacy has been compromised, potentially resulting in losses for bidders and others. This research aims to improve the current practice of real estate EAuctions in Malaysia, with a particular emphasis on the High Court of Malaya E-Auction. Thus, the research objective to be met is to propose the improvements to the practice of real estate E-Auction in Malaysia. Meanwhile, the methodology for this research is based on primary data, which includes journal, book, conference, and seminar papers, by provides a set of questionnaires to the respondents from the public, bidders, and auctioneers themselves. The questionnaire was circulated using Google Forms, and two hundred fourteen (214) individuals participated in the survey as panel in the auction sector. The acquired data would be analysed using descriptive, crosstab, and content analysis. As a result, the research discovered a need to strengthen the auction industry, particularly the E-Auction System High Court of Malaya, in order to guarantee that the real estate auction sector remains relevant and contributes to Malaysia's economic development.